The Impact Of Changes In Company Financial Performance On Company Financial Reports - Nabila Syaharani; Elsa Nasution; Liza Seftina; Esra Yanti Sibarani; Fitri Yani Panggabean (Sean Institute, 2025)
This study examines the impact of changes in company financial perfor-mance on company financial reports, Financial performance plays a crucial role in deter-mining a company's financial health, stability, and investment potential. Key financial indicators such as liquidity, profitability, solvency, and efficiency are essential for evaluat-ing corporate success and sustainability. The research employs a quantitative approach, analysing financial ratios derived from company financial reports. Indicators such as Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Cur-rent Ratio (CR) are used to measure the relationship between financial performance and changes in financial reports. Multiple regression analysis is applied to assess the signifi-cance of these factors. The findings indicate that fluctuations in profitability and solvency have the most significant impact on company financial reports, influencing investor con-fidence and corporate decision-making. Companies with higher profitability ratios tend to report improved financial stability, while excessive debt levels negatively affect finan-cial statements. Liquidity, although essential for short-term obligations, shows a varied effect depending on asset utilization and operational efficiency. This study provides val-uable insights for corporate management, investors, and policymakers in understanding how financial performance changes reflect in financial reports. Effective financial man-agement and strategic decision-making are crucial in ensuring business sustainability and long-term value creation.